Understanding H-type anorectal malformation in females for a suitable surgical approach – A single center experience from central India - Samir Kant Acharya; Goutam Chakraborty; Amit Kumar Jadhav; Nidhi Sugandhi; Deepak Bagga; Rajat Piplani (Indian Journal of Child Health, 2020)
Background: H-type anorectovestibular fistula is a rare anorectal malformation (ARM) in females where the child passes stool through a vestibular opening in addition to the normal anus. The diagnosis is easy and largely clinical but controversies exist regarding the most suitable surgical approach and technique to minimize complications. Objectives: This study aims to discuss the different possible presentations of the anomaly and the most suitable surgical approach to it. Materials and Methods: We analyzed a total of ten patients with this condition treated over a period of 3 years from January 2017 to December 2019. All underwent definitive surgery by the anterior perineal approach without any protective colostomy. They were analyzed with respect to age, presentation, coanomalies, fistula location, internal opening to anus distance, wound related complications or recurrence, need for colostomy later, and presence of constipation over 8 months of follow-up. Results: Incidence was 8.77% (10/114) of all ARMs in females. Mean age at presentation was 47.1 days and 3 (30%) had coanomalies. Vestibular staining was the most common manifestation. Mean internal opening to anus distance was 2.04 cm. Two (20%) had wound breakdown postoperatively and one (10%) had recurrence in long-term follow-up. These patients underwent colostomy. Two had constipation but all allowed adequate dilatation during mean follow-up of 8 months. Conclusion: H-type ARM in females can be suitably managed with the anterior approach. However, a proximal colostomy appears to significantly decrease the complication rate of the definitive surgery.